2009
DOI: 10.1021/cg900573w
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Salicylic Acid Molecules into the Intermolecular Spaces of γ-Cyclodextrin-Polypseudorotaxane

Abstract: Sealed-heating of salicylic acid (SA) and polyethylene glycol (PEG)/γ-cyclodextrin (CD)-polypseudorotaxane induced a novel complex formation wherein SA was inhabited in the intermolecular spaces formed by the γ-CD/polypseudorotaxane columns. Incorporation of SA into the PEG/γ-CD-polypseudorotaxane structure was clarified by powder X-ray diffraction measurements and 13 C-solid-state NMR spectroscopy. Different water vapor adsorption and desorption behaviors between the novel complex and PEG/ γ-CD-polypseudorota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
111
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(119 citation statements)
references
References 33 publications
7
111
1
Order By: Relevance
“…Furthermore, some interesting abilities of cyclodextrins, such as permeability enhancer, could be evaluated by quantifying cyclodextrin content before and after their passage through a cell layer (Matilainen et al, 2008). Since Nuclear Magnetic Resonance (NMR) spectroscopy is one of the most widely used techniques for understanding the interaction between CD and guest compounds (Bertholet et al, 2005;Higashi et al, 2009;Lis-Cieplak et al, 2014;Malet-Martino and Holzgrabe, 2011;Schneider et al, 1998;Vogt and Strohmeier, 2012;Yang et al, 2009) and to evaluate the number of substituted glucopyranose units (molar substitution), we aim to apply 1 H nuclear magnetic resonance spectroscopy ( 1 H NMR) to quantify 2-HP-b-CD in pharmaceutical solutions. Under controlled conditions, 1 H NMR spectroscopy is considered as quantitative given that the intensity of a signal is directly related to the amount of resonant nuclei (Holzgrabe et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some interesting abilities of cyclodextrins, such as permeability enhancer, could be evaluated by quantifying cyclodextrin content before and after their passage through a cell layer (Matilainen et al, 2008). Since Nuclear Magnetic Resonance (NMR) spectroscopy is one of the most widely used techniques for understanding the interaction between CD and guest compounds (Bertholet et al, 2005;Higashi et al, 2009;Lis-Cieplak et al, 2014;Malet-Martino and Holzgrabe, 2011;Schneider et al, 1998;Vogt and Strohmeier, 2012;Yang et al, 2009) and to evaluate the number of substituted glucopyranose units (molar substitution), we aim to apply 1 H nuclear magnetic resonance spectroscopy ( 1 H NMR) to quantify 2-HP-b-CD in pharmaceutical solutions. Under controlled conditions, 1 H NMR spectroscopy is considered as quantitative given that the intensity of a signal is directly related to the amount of resonant nuclei (Holzgrabe et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…23 Our recent study showed that sealedheating of salicylic acid (SA) with PEG/g-CD polypseudorotaxane induced a novel complex formation. 24 In this complex, each g-CD molecule can be inhabited by two SA molecules in the intermolecular spaces between the PEG/g-CD-polypseudorotaxane columns.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent study, it was found that the sealed-heating of salicylic acid (SA) with polyethylene glycol (PEG)/g-CDpolypseudorotaxane induced complex formation. 14) In this complex, two SA molecules for each g-CD molecule were incorporated into the intermolecular spaces between the columns of g-CD stacks, while double-stranded PEG chains were included in the g-CD cavity. Although a large number of studies have been carried out on the inclusion complexes of CDs, there are only a few reports on the existence of guest molecules outside the CD cavity.…”
mentioning
confidence: 99%
“…The diffraction pattern of the SH was similar to that of the monoclinic columnar form reported previously. 14,25) We have proposed that the transformation from the hexagonal columnar form to the monoclinic columnar form takes place upon the complex formation of SA/(PEG/g-CD-polypseudorotaxane) by the sealed-heating method.…”
mentioning
confidence: 99%
See 1 more Smart Citation